(untitled) - Whitney, Donald S. (Singapore, 1992)
Ideal for personal or small-group use, this companion guide to Spiritual Disciplines for the Christian Life takes you through a carefully selected array of disciplines that will help you be more like Jesus.
Keywords: Spiritual life -- Christianity; Discipline -- Religious aspects -- Christianity